The acne positivity movement of beauty influencers (instagram @ratughania qualitative content analysis) - Yahdini, Azka Tsania; Ulyanada, Febriandini Nisa; Dwiningtyas, Hapsari (Institute of Computer Science (IOCS), 2024)
The acne positivity movement is a movement that voices that acne as a type of skin problem, is a normal thing and not a shameful thing. This movement leads to the spread of messages and motivations to others to love themselves no matter what the conditions. One of Indonesia's beauty inluencers who quite often conveys messages about acne positivity on Instagram is Ratu Ghania (@ratughania). This study will use qualitative content analysis methods to analyze posts listed in @ratughania Instagram account to find out the type of content, audience response, and the meaning of the message behind the photos and captions uploaded by @ratughania Instagram account. Instagram was chosen as the data source because it is a popular social media that is widely used to spread many movements or campaigns including acne positivity. The theories used in this study are Social Media Theory, Influencer Concept, and Standpoint Theory. The results of this study then found three categories in Instagram content from @ratughania namely confidence, motivation, and self-defense. The trio explains how social media and influencers have the power to influence audience perspectives, and shows how the courage of women with marginalized acne-prone skin fights against the social construction of beautiful women in society